2012
DOI: 10.1016/j.nutres.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training blocks uncoupling protein 1 up-regulation in brown adipose tissue while increasing uncoupling protein 3 in the muscle tissue of rats fed with a high-sugar diet

Abstract: The mitochondrial uncoupling proteins (UCPs) of interscapular brown adipose tissue (iBAT) and of muscles play important roles in energy balance. For instance, the expression of UCP1 and UCP3 are modulated by free fatty acid gradients induced by high-sugar diets and acute exercise that is dependent on sympathetic stimulation. However, the effects of endurance training in animals fed with high-sugar diets are unknown. This study aims to evaluate the long-term effects of diet and exercise on UCP1 and UCP3 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 87 publications
4
42
0
Order By: Relevance
“…The high-sugar diet consisted of 33% standard chow (Nuvilab®CR1; Nuvital, Brazil), 33% condensed milk and 7% sucrose by weight (the remaining is water; de Queiroz et al, 2012). The energy density was 12.26 kJ/g for the standard chow diet and 13.35 kJ/g for the high-sugar diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-sugar diet consisted of 33% standard chow (Nuvilab®CR1; Nuvital, Brazil), 33% condensed milk and 7% sucrose by weight (the remaining is water; de Queiroz et al, 2012). The energy density was 12.26 kJ/g for the standard chow diet and 13.35 kJ/g for the high-sugar diet.…”
Section: Methodsmentioning
confidence: 99%
“…The energy intake was measured as follows: amount of food intake × energy density of the diets (de Queiroz et al, 2012). The animals were euthanized under fed conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies performed by our group demonstrated that rats fed an HSD and subjected to running training for an 8-week period had the relationship between the Ucp1 / Ucp3 mRNA levels impaired. This change may result in lower energy efficiency and may also explain the increase in the adipose index observed in these animals because exercise training blocked the HSD-induced up-regulation of UCP1 expression in iBAT and up-regulated the Ucp3 mRNA levels in muscle tissues [28]. Thus, the hypothesis examined in this study was that exercise does not attenuate the effects of an HSD on fat cell size and lipid content, and the mechanism of action involved in this process is mediated by leptin through its receptors in adipocytes, which involves the regulation of the TAG synthesis and storage/lipolysis pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The retroperitoneal fat pad was chosen because it is one of the major sites of leptin production in rodents [29], and it may be related to the metabolic complications of obesity [30]. Furthermore, the retroperitoneal fat pad is very responsive to diet interventions [28, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…It is defined as an adaption to defend against cold and maintain body temperature via the uncoupling of protein 1, in contrast to the function of white adipocytes, which is to store energy [23]. Previous reports also show that training enhances the regulation of Ucp1/Ucp3 mRNA, which could result in higher energy efficiency [6]. In the current study, ET+CCP treatment may induce an increased activation when compared to treatment with ET and result in a marked elevation in BAT weight, which leads to better metabolic or energy efficiency.…”
Section: Discussionmentioning
confidence: 99%